Outer membrane vesicles of Tannerella forsythia: biogenesis, composition, and virulence. (16th June 2015) - Friedrich, V.; Gruber, C.; Nimeth, I.; Pabinger, S.; Sekot, G.; Posch, G.; Altmann, F.; Messner, P.; Andrukhov, O.; Schäffer, C.
Summary: Tannerella forsythia is the only 'red‐complex' bacterium covered by an S‐layer, which has been shown to affect virulence. Here, outer membrane vesicles (OMVs) enriched with putative glycoproteins are described as a new addition to the virulence repertoire of T. forsythia . Investigations of this bacterium are hampered by its fastidious growth requirements and the recently discovered mismatch of the available genome sequence (92A2 = ATCC BAA‐2717) and the widely used T. forsythia strain (ATCC 43037). T. forsythia was grown anaerobically in serum‐free medium and biogenesis of OMVs was analyzed by electron and atomic force microscopy. This revealed OMVs with a mean diameter of 100 nm budding off from the outer membrane while retaining the S‐layer. An LC‐ESI‐TOF/TOF proteomic analysis of OMVs from three independent biological replicates identified 175 proteins. Of these, 14 exhibited a C‐terminal outer membrane translocation signal that directs them to the cell/vesicle surface, 61 and 53 were localized to the outer membrane and periplasm, respectively, 22 were predicted to be extracellular, and 39 to originate from the cytoplasm. Eighty proteins contained the Bacteroidales O ‐glycosylation motif, 18 of which were confirmed as glycoproteins. Release of pro‐inflammatory mediators from the human monocytic cell line U937 and periodontal ligament fibroblasts upon stimulation with OMVs followed a concentration‐dependent increase that was more pronounced in the presence of soluble CD14 in conditioned media. The inflammatory response was significantly higher than that caused by whole T. forsythia cells. Our study represents the first characterization of T. forsythia OMVs, their proteomic composition and immunogenic potential.